2015
DOI: 10.1186/s12941-015-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of native California medicinal plant extracts isolated from Rhamnus californica and Umbellularia californica

Abstract: BackgroundAntimicrobial resistance (AMR) is a major threat to global public health. Medicinal plants have long been used as remedies for infectious diseases by native cultures around the world and have the potential for providing effective treatments for antibiotic-resistant infections. Rhamnus californica (Rhamnaceae) and Umbellularia californica (Lauraceae) are two indigenous California plant species historically used by Native Americans to treat skin, respiratory and gastrointestinal infections. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…The antibacterial activity of the extracts against K. pneumoniae is noteworthy because plant extracts and their compounds have previously been reported to be more active against Gram-positive bacteria than Gram-negative ones 24. Our results are also in agreement with the previous reports 25 of Carranza et al (2015) who have shown a significant antibacterial activity of the leaf extract of Rhamnuscalifornica against two bacterial pathogens with the zones of inhibition ranging from 10.0 ± 2.1 to 14.0 ± 1.4 (mm). Similarly, the crude extract obtained from a Rhamnous member Ventilago madraspatana has been shown to have broad-spectrum antimicrobial activity against a panel of Gram positive, Gramnegative bacteria and Candida pathogens 26.…”
Section: Discussionsupporting
confidence: 93%
“…The antibacterial activity of the extracts against K. pneumoniae is noteworthy because plant extracts and their compounds have previously been reported to be more active against Gram-positive bacteria than Gram-negative ones 24. Our results are also in agreement with the previous reports 25 of Carranza et al (2015) who have shown a significant antibacterial activity of the leaf extract of Rhamnuscalifornica against two bacterial pathogens with the zones of inhibition ranging from 10.0 ± 2.1 to 14.0 ± 1.4 (mm). Similarly, the crude extract obtained from a Rhamnous member Ventilago madraspatana has been shown to have broad-spectrum antimicrobial activity against a panel of Gram positive, Gramnegative bacteria and Candida pathogens 26.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, these biomolecules possess a wide spectrum of chemical properties including unique chemical scaffolds and complex structures, providing potentiating inhibitory effects associated with possible distinctive mechanisms of action against microorganisms [15,16]. There have been several previous studies reporting a significant advantage of these phytochemicals to impede the development of drug-resistant bacteria [17,18]. Some of these phytochemicals and plant extracts are designated by the United States Food and Drug Administration (FDA) as Generally Recognized As Safe (GRAS), and have low toxicity and good acceptability to food and medical applications [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofloxacin antibiotic disc inhibition zone diameters were 22 mm, 0 mm, 30 mm, 0 mm, 30 mm, and 28 mm for S. pneumoniae, E. coli, S. aureus, P. aeruginosa, B. subtilis, and K. pneumoniae, respectively. The extract of R. californica leaves was the most active among the three extracts, whereby the strongest effect was noted on the only antibiotic-resistant strain tested, MRSA 23 . C. sinensis extract-AgNPs have also shown potent antimicrobial activity against pathogenic bacteria 20 .…”
Section: Antimicrobial Activitymentioning
confidence: 96%